Phytochemical Screening and Antioxidant Activity Test of Red Onion (Allium ascolinicum L.) Extract Variety of Palu Valley - Rimah Juwita; Daud K. Walanda; Supriadi Supriadi (Jurnal Akademika Kimia, 2020)
The red onion of Palu valley variety is a plant that is widely found in Palu area and regarded as a leading commodity in Central Sulawesi. The purpose of this study was to examine the secondary metabolite compounds contained in red onion (Allium ascolinicum L.) of Palu valley variety and its antioxidant activity. Antioxidant activity test in this study used DPPH (1,1-Diphenyl-2-Pikrilhidrazil) as a source of free radical, and vitamin C as the comparison. The antioxidant activity of red onion extract was analyzed using a UV-Vis spectrophotometer. The red onion tuber powder was extracted by maceration using ethanol solvent. Qualitative test of onion powder showed positive results on alkaloids, flavonoids, and tannin compounds. The samples and vitamin C were tested for antioxidant activity in various extract concentrations of 10, 30, 50, 70, and 90 ppm. The results showed that red onion extract of Palu valley variety presented an IC50 value of 38.548 ppm, and vitamin C presented an IC50 value of 22.646 ppm. Based on these values, the red onion (Allium ascolinicum L.) extract is categorized as a very strong class of antioxidant which can be used as a source of natural antioxidant.